2021
DOI: 10.1007/s00467-021-04949-5
|View full text |Cite
|
Sign up to set email alerts
|

Kidney disease in children with heart or liver transplant

Abstract: Over the past few decades, there has been increasing recognition of kidney disease in children with non-kidney solid organ transplantation. The risk of kidney disease in children undergoing heart or liver transplantation is higher than the general population as the underlying disease and its associated management may directly impair kidney function. Both heart and liver failures contribute to hypoperfusion and kidney ischemia before patients reach the point of transplant. The transplant surgery itself can ofte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 82 publications
(148 reference statements)
0
15
0
Order By: Relevance
“…Given the harmful consequences of AKI, AKI‐6 can accurately identify and stratify patients at risk of developing inferior outcomes, allowing clinicians to optimize strategies to prevent AKI or minimize AKI severity 1–10 . For recipients with pediatric HT, such strategies may include supporting renal perfusion through hemodynamic management, minimizing the use of nephrotoxic medications, and pharmacoprophylaxis with aminophylline to reduce the incidence of AKI 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the harmful consequences of AKI, AKI‐6 can accurately identify and stratify patients at risk of developing inferior outcomes, allowing clinicians to optimize strategies to prevent AKI or minimize AKI severity 1–10 . For recipients with pediatric HT, such strategies may include supporting renal perfusion through hemodynamic management, minimizing the use of nephrotoxic medications, and pharmacoprophylaxis with aminophylline to reduce the incidence of AKI 19 .…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In the pediatric heart transplant (HT) population, persistent AKI has been associated with an increased risk of CKD within the first year after the transplant. [8][9][10] Given the associations between AKI and clinical outcomes in this population, a more nuanced understanding of AKI severity may allow clinicians to better identify patients at greatest risk for inferior post-HT outcomes. AKI may manifest as elevated serum creatinine (SCr), decreased urine output (UO), or both.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In single-center studies, perioperative AKI has been reported in 67%-73% of pediatric heart recipients and 46%-67% of pediatric liver recipients. 28 Post-transplant, prolonged calcineurin inhibitor toxicity is a significant contributor to kidney dysfunction, particularly in the setting of chronically high tacrolimus trough levels. Tacrolimus decreases glomerular blood flow and stimulates production of the pro-fibrotic cytokine transforming growth factorβ, leading to renal interstitial fibrosis.…”
Section: Chroni C K Idne Y D Is E a S E In Non -Kidne Y Sotmentioning
confidence: 99%
“…The effects of CKD in adult LT recipients include cardiovascular complications, which in turn aggravate renal impairment in the long term 3 . The effects of posttransplant CKD are even greater in children, as they also impact growth and development and put them at risk for future renal failure 4 . It is, therefore, important to prevent renal damage in these patients and monitor renal function during follow‐up in order to treat the possible underlying renal pathology and attenuate further demise.…”
Section: Introductionmentioning
confidence: 99%